The use of vitamin C in the intensive care unit during the COVID-19 pandemic - Ozgunay, Seyda Efsun; Ceylan, İlkay; Ökmen, Korgün; Sayan, Halil Erkan; Eminoglu, Şermin; Karasu, Derya; Yavuz, Senol (The European Research Journal, 2021)
Objectives: An exaggerated inflammatory immune response is observed in cases of COVİD 19. This study aims to evaluate the effects of vitamin C, as a significant modulator of inflammation, on the inflammatory parameters and mortality in patients followed up in the intensive care unit (ICU) during the pandemic. Methods: This single-center retrospective study included 160 adult patients with confirmed positive nasopharyngeal smear COVID-19 PCR test results, who were followed up in the ICU between 01 March and 01 August 2020. Hospital files were scanned and patients given and not given vitamin C were assigned, to Group 1 and Group 2, respectively. The Acute Physiology and Chronic Health Evaluation (APACHE II) scores, the data entries on demographics, ventilation, laboratory tests, duration of ICU stay, discharge, and mortality were compared. Interventions with antiviral and antibacterial agents. steroids, cytokine apheresis, and renal replacement therapy were evaluated. Results: Vitamin C treatment was started in patients with raised neutrophil/lymphocyte ratio (NLR) at admission to ICU, who made up 20% of the total 160 ICU patients. Mortality incidence was higher among patients with raised NLR. Vitamin C at the doses used did not affect the inflammatory parameters, length of stay or mortality, and 37.5% of the patients recovered and were discharged from the ICU. Conclusions: We think that vitamin C treatment will have positive effects on the initiation of COVID-19 and that the time of intiation of the therapy and the optimal doses used should be determined with prospective studies.